2007
DOI: 10.1063/1.2722310
|View full text |Cite
|
Sign up to set email alerts
|

Gain and efficiency enhancement of a Cerenkov free electron laser by a prebunched electron beam in a dielectric loaded waveguide

Abstract: A density prebunched electron beam on a Cerenkov free electron laser (CFEL) offers considerable enhancement in gain and efficiency in a dielectric loaded waveguide. The growth rate, efficiency, and gain were evaluated based on experimentally known parameters relevant to the CFEL. It was found that the growth rate, efficiency, and gain of the CFEL increase with the modulation index and has the largest value when the modulation index approaches unity in addition to the frequency and wave number of the prebunched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In their analysis, they neglected the space charge effect and performed the calculations only in the low-gain regime. The analysis was further extended by several authors [5][6][7][8][9][10] by setting up the coupled Maxwell-Vlasov equations, and the growth rate was calculated. In most of the earlier analyses, the electron motion was assumed to be one dimensional in the presence of strong external static magnetic field [3][4][5]15].…”
Section: Introductionmentioning
confidence: 99%
“…In their analysis, they neglected the space charge effect and performed the calculations only in the low-gain regime. The analysis was further extended by several authors [5][6][7][8][9][10] by setting up the coupled Maxwell-Vlasov equations, and the growth rate was calculated. In most of the earlier analyses, the electron motion was assumed to be one dimensional in the presence of strong external static magnetic field [3][4][5]15].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The use of a pre-bunched electron beam in free-electron lasers leads to coherent emission with reduction in the accumulation time of the radiation. [21,22] Sharma and Bhasin [23] studied the effect of beam pre-bunching on the Cerenkov free-electron laser and found that significant improvement in gain and efficiency can be achieved if the frequency of the modulated electron beam becomes comparable to that of radiation wave.…”
Section: Introductionmentioning
confidence: 99%
“…The emission of high‐power terahertz (THz) radiation from a free‐electron laser (FEL) using a pre‐bunched electron beam has been a field of interest for several years due to its potential applications in diverse areas including spectroscopy, medicine, security, and defense . Pre‐bunching of the beam leads to coherent emission of the radiation with enhanced power and efficiency …”
Section: Introductionmentioning
confidence: 99%